2014
DOI: 10.1093/jxb/eru290
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of a polytopic membrane protein to the inner envelope membrane of chloroplasts in vivo involves multiple transmembrane segments

Abstract: Highlight textThis work demonstrated that the targeting of a polytopic membrane protein to the inner envelope membrane of chloroplasts in vivo involves multiple transmembrane segments including the indispensable transmembrane segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…1). According to our previous study 12 , the topology of K124 has been shown to be flipped at the IEM, and the C-terminus faces toward the stroma. Hence, we assumed that the topology of a bicarbonate transporter fused to K124, SbtAIII, is reverted, as compared to that fused to the full-length Cor413im1, SbtAII 10 .…”
Section: Co-expression Of Chimeric Bicarbonate Transporters and Tev Pmentioning
confidence: 77%
See 2 more Smart Citations
“…1). According to our previous study 12 , the topology of K124 has been shown to be flipped at the IEM, and the C-terminus faces toward the stroma. Hence, we assumed that the topology of a bicarbonate transporter fused to K124, SbtAIII, is reverted, as compared to that fused to the full-length Cor413im1, SbtAII 10 .…”
Section: Co-expression Of Chimeric Bicarbonate Transporters and Tev Pmentioning
confidence: 77%
“…The antibodies against LSU, Tic110, and Toc75 have been previously described 10,12,28,[31][32][33] . The LHCP antibodies were a kind gift from Prof. Kenneth Cline.…”
Section: Analysis Of the Localization Of Each Chimeric Protein Withinmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they may be subject to lateral insertion into the envelope membranes. Specific mitochondrial and chloroplast proteins are proposed to be inserted into the outer or inner envelope membrane by lateral translocation from the import channel (Viana et al, 2010;Okawa et al, 2014;Harner et al, 2011), and endoplasmic reticulum membrane proteins are laterally translocated from import channels to membranes (Ismail et al, 2012). The lateral translocation of inefficiently translocating preproteins with TMDs to outer envelope membranes may constitute a mechanism by which the import channel is preserved for efficient translocation of cargoes.…”
Section: Discussionmentioning
confidence: 99%
“…It is not fully understood how the pulling process occurs in chloroplasts, or whether TPs contain any sequence motifs that direct the pulling. Chloroplasts import soluble and membrane proteins that contain transmembrane domains (TMDs; Okawa et al, 2014;Viana et al, 2010;Froehlich and Keegstra, 2011;Lee et al, 2017). The mechanistic function of chloroplast import channels is not fully understood, and it is possible that specific properties of the polypeptides that pass through the import channels may affect their translocation.…”
mentioning
confidence: 99%